ONLINE MARKETING APPLICATION DEVELOPMENT TO EXPAND THE MARKET OF MALANG’S LOCAL PRODUCTS - diah priharsari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
Internet is a great tool to be introduced to SMME (Small Micro Medium Enterprises) as an alternative to promote their products. This program is done to introduce and create an opportunity for several choosen SMMEs to advertise their products through the internet. There are three SMMEs that are selected based on HWPRI reccomendation to be utilized with e-commerce. They are Niwa Crafting, Gazatri Art, and Preman Super. E-commerce and pheripherals to access internet are provided for them. In the end of the program, after receiving software and hardware, the three SMMEs are enthusiasm to receive the programs. However, further investigation is needed to understand the nature of the SMME in using the internet.